Comparison of aminotransferase activity in patients with rhabdomyolysis due to acute intoxication with psychotropic and chemical substances - Babulovska, Aleksandra; Chaparoska, Daniela; Velikj Stefanovska, Vesna; Simonovska, Natasha; Pereska, Zanina; Kostadinoski, Kristin; Naumovski, Kiril (GUARANT International spol. s r.o., 2021)
Aims: We determine the aminotransferase activity in patients with rhabdomyolysis following acute intoxication with psychotropic and chemical substances. Methods: In a clinically controlled prospective study, 140 patients with rhabdomyolysis were divided into two groups depending on the intoxicating substance i.e. psychotropic or chemical. Rhabdomyolysis was defined according to the poisoning severity score. To distinguish whether elevated AST and ALT are attributed only to muscle injury or concomitant liver damage, serum levels of AP, GGT, bilirubin, albumin, and prothrombin time were analyzed. Data were statistically analyzed in SPSS software, version 22.0 for Windows (SPSS, Chicago, IL, USA). Results: In acutely intoxicated patients with rhabdomyolysis, 60% had increased AST values, in the group with psychotropic intoxications, AST values were elevated by 43%, and in the group, with chemical intoxication, 17% of the subjects had elevated AST levels. Patients with rhabdomyolysis due to psychotropic intoxication on the fifth day have significantly higher AST (p = 0.0138) and ALT (p = 0.0129) than patients with chemical intoxication. The CPK / AST correlation on the first day was significantly stronger in psychotropic compared to chemical intoxications (p = 0.0009). In psychotropic intoxications we found significant linear positive moderate correlation (p = 0.0001) and in chemical intoxications non-significant linear positive had a very weak correlation (p = 0.003). With increasing CPK, ALT was significantly increased in psychotropic intoxication and was slightly increased in patients with chemical intoxication. Conclusion: Changes in AST and ALT values were correlated with CPK values, suggesting that elevated aminotransferases in rhabdomyolysis in those intoxicated with psychotropic substances may indicate skeletal muscle damage rather than hepatocyte damage. Elevated aminotransferases in chemical intoxications are due to the hepatotoxic effects of certain substances or can accompany severe clinical presentation with multiorgan failure. Intoxications with mushrooms, gasoline, corrosives, are the typical offending agent.
Keywords: aminotransferase; rhabdomyolysis; psychotropic substances; chemical substances